2008
DOI: 10.1159/000135613
|View full text |Cite
|
Sign up to set email alerts
|

Imaging Epileptic Activity Using Functional MRI

Abstract: This review concentrates on functional MRI (fMRI) methods to identify the epileptic focus, i.e. ictal and interictal fMRI. First, established clinical applications of fMRI in the field of epilepsy are briefly introduced: fMRI of sensorimotor, language and memory function can already be considered as clinically relevant tools to identify the eloquent cortex and to predict postoperative functional deficits in patients considered for epilepsy surgery. fMRI offers a valid alternative to invasive methods like the W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 132 publications
0
12
0
Order By: Relevance
“…Currently, the most specific clinical method to pinpoint the seizure source consists of using volume conduction to model ECoG potentials recorded over the suspected cortical area [48, 49, 50]. The neurosurgeon first identifies the electrode recording abnormal activity, then proceeds with the removal of the underlying cortical region.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, the most specific clinical method to pinpoint the seizure source consists of using volume conduction to model ECoG potentials recorded over the suspected cortical area [48, 49, 50]. The neurosurgeon first identifies the electrode recording abnormal activity, then proceeds with the removal of the underlying cortical region.…”
Section: Discussionmentioning
confidence: 99%
“…There was the hope of providing useful clinical information particularly in patients undergoing pre-surgical evaluation. A detailed discussion of the literature is beyond the scope of this article and can be found in reviews (Cunningham et al, 2008;Gotman, 2008;Gotman et al, 2006;Gotman and Pittau, 2011;Hamandi et al, 2004;Krakow, 2008;Laufs and Duncan, 2007;Richardson, 2010;Rosenkranz and Lemieux, 2010;Salek-Haddadi et al, 2003;Stern, 2006;Yu et al, 2005). In summary, research advanced from feasibility studies Hamandi et al, 2004;Lemieux, 2004;Salek-Haddadi et al, 2003;Stern, 2006;Yu et al, 2005) to those attempting to identify the irritative zones in individual or cohorts of patients with focal Krakow et al, 1999;Patel et al, 1999;Salek-Haddadi et al, 2006) or generalized epilepsy syndromes (Aghakhani et al, 2004;Hamandi et al, 2006), or patients with a particular type of pathology (Federico et al, 2005b;Kobayashi et al, 2007;Kobayashi et al, 2006b;Kobayashi et al, 2005).…”
Section: Eeg-fmri Applications In Epilepsymentioning
confidence: 99%
“…Several studies have shown that the coregistration of EEG and fMRI (EEG-fMRI) is applicable for the identification of the epileptic focus [e.g. Benar et al, 2002;Gotman et al, 2004;Krakow 2008;Salek-Haddadi et al, 2006;Zijlmans et al, 2007]. From the EEG a reference function is extracted, representing the occurrence of the interictal epileptiform discharges (IED).…”
Section: Introductionmentioning
confidence: 99%